Exploring Students’ Challenges in Reading English Short Stories: Insight and Solutions - Nurrahmah, Fitriyani; Mazriya, Nandini Putri; Khaerani, Putri; Adilla, Rifa; Maulidya, Reza Anis; Hidayat, Didin Nuruddin; Mulyati, Yatni Fatwa (Jurnal Basicedu, 2023)
The declining enthusiasm for reading among university students poses diverse challenges in educational research. This study aims to investigate the barriers faced by literature education students when reading English short stories from https://read.gov/aesop/ and their strategies to overcome these challenges. Using a qualitative approach with a descriptive design, this study presents insights gathered from 43 students at one state university in Indonesia. Furthermore, a questionnaire was administered to explore the challenges faced during the learning process and measure whether those barriers impacted their reading interest. The findings indicate several barriers, such as deciphering figurative language, understanding unfamiliar vocabulary, and grappling with complex grammatical structures. In addition, students' motivation to overcome challenges in understanding English short stories was affected by their inadequate knowledge of English vocabulary, which hindered their ability to construct coherent meanings. The findings also show some solutions to overcome the difficulties in reading English short stories, such as asking friends or lecturers for word meanings and using translation tools to find out the meaning of unknown words. Based on the results of the study, it can be concluded that the difficulties arising from reading English short stories can be resolved with various solutions that have been found.